HEPATORENAL SYNDROME IN PATIENTS WITH CIRRHOSIS OF LIVER ACCORDING TO 2007 INTERNATIONAL ASCITES CLUB CRITERIA - Seetlani, Naresh Kumar; Memon, Abdul Rauf; Iftikhar, Fahmeen; Ali, Asif; Fazel, Pyar Ali (Journal of Ayub Medical College Abbottabad, 2016)
Background: Heptorenal syndrome is a complication of cirrhosis of liver and is characterized by progressive renal failure. This study was done to determine the frequency of hepatorenal syndrome according to 2007 international ascites club criteria among patients of cirrhosis attending Medical Units of Civil hospital Karachi. Methods: This is a cross-sectional study conducted on the hospitalized patients in the Department of Medicine-Civil Hospital Karachi from 01-04-2014 to 30-09-2014 where total 265 patients of either gender, age >18 years & <60 years & diagnosed case of CLD were included. Patients with shock, SIRS, sepsis, known cases of intrinsic renal diseases, or history of diabetes mellitus, Hypertension or connective tissue diseases were excluded. Mean±SD were expressed for continuous variable like, age, duration of CLD. Frequency & percentages of other categorical variables, i.e., gender, residence were expressed. Effect modification was tested through Chi-square with p-value <0.05 significant. Results: The mean±SD age of patient was 48.23±7.87 years with range 18-60 years. Mean±SD duration of chronic liver disease was 5.60±1.92 years with a range of 3-12 years. More than 155 (58%) participants in this study were male and females were 110 (41.51%). More than 36 (13%) were of age less than and equal to 40 years; 121 (45.67%) were from 41-50 years, while 108 (40.75%) were from age 51-60 years. More than 176 (66.41%) belonged to rural areas while only 89 (33.58%) belonged to urban areas. The study observed that according to IAC 2007 criteria of diagnosis of hepatorenal syndrome 15.09% of patients with cirrhosis were found to have HRS. Conclusion: Hepatorenal syndrome represents the end stage of a sequence of reduction of renal perfusion induced by advanced liver failure. Almost every seventh patient of Cirrhosis can develop hepatorenal Syndrome. This should be looked up at an early stage so that it can be prevented. Keywords: Hepatorenal Syndrome; renal failure; Cirrhosis